Successful treatment discontinuation in CML patients with full-dose and low-dose TKI: Results from real-world practice - Chen, Yilin; Zhao, Huifang; Guo, Jingming; Zou, Jing; He, Wenjuan; Han, Danlei; Cheng, Fanjun; Zhang, Yanli; Li, Weiming (Frontiers in Pharmacology, 2023)
Background: In clinical studies, some patients who achieve deep molecular response (DMR) can successfully discontinue tyrosine kinase inhibitor (TKI). TKI dose reduction is also an important aspect of alleviating adverse effects and improving quality of life. This study aimed to explore the outcome after drug withdrawal in Chinese CML patients. Methods: We conducted a retrospective analysis of the outcome of 190 patients who stopped TKI. 27 patients experienced dose reduction before TKI discontinuation. The median duration of TKI treatment and MR4 before discontinuation was 82 months and 61 months. Results: With median follow-up after stopping TKI treatment of 17 months, the estimated TFR (Treatment Free Remission) were 76.9% (95%CI, 70.2%–82.4%), 68.8% (95%CI, 61.3%–75.2%), and 65.5% (95%CI, 57.4%–72.5%) at 6, 12 and 24 months. For full-dose and low-dose TKI groups, the TFR at 24 months was 66.7% and 55.8% (p = 0.320, log-rank). Most patients (56/57) quickly achieved MMR after restarting TKI treatment. Multivariable analysis showed that patients with TKI resistance had a higher risk of molecular relapse than patients without TKI resistance (p < 0.001). Conclusion: TFR rates were not impaired in patients experiencing dose reduction before TKI discontinuation compared to patients with full-dose TKI. Our data on Chinese population may provide a basis for the safety and feasibility of TKI discontinuation, including discontinuation after dose reduction, in clinical practice.